IMAGE INFORMATION VALUE OF VARIATION ANALYSIS VALUE SENSITIVIY ENCHODING (SENSE) USING T2 WEIGHTED TURBO BALANCE FIELD ECHO (BTFE) SEQUENCE IN THE MRCP IN RADIOLOGICAL INSTALLATION SILOAM HOSPITAL SURABAYA - Ary Indra Wicaksono; Emi Murniati; Siti Masrochah (Poltekkes Kemenkes Semarang, 2018)
Background : MRCP is an examination used to evaluate the system billiary, pancreas and gall bladder with channel because of the possible presence of stones, tumors and other diseases. To diagnose the MRCP examination,one sequence in use is T2 weighted Turbo Field Echo Balance (T2W BTFE) which in its parameters No Sensitivity Enchoding (SENSE). The purpose of this study was to determine the Information analysis Anatomical differences with variation of Sensitivity Encoding (SENSE) on T2-weighted sequences BTFE the MRCP examination, And to investigate value Sensitivity Encoding (SENSE) optimal T2-weighted sequences BTFE the MRCP examination.Methods : The method of this research is experimental with approach quasi-experimental design with control. This research is done in Siloam Hospital Surabaya. MRCP image data in the form of axial 40 of the 10 patients with 4 variation of Sensitivity Encoding (SENSE), which are 1.4, 1.6, 1.8, and 2. Assessment of information image data done by 3 respondents. Analysing process done with Friedman test.Results : The results showed that there MRCP image information differences with variation in sensitivity encoding (SENSE) on T2-weighted sequences BTFE with a significance level of p value 0.001. Differences in image information occurs in liver, Gall Blader, Pancreas and CBD (Common Bile Duct). The use value Sensitivity Encoding (SENSE) on T2-weighted sequences for optimal BTFE MRCP is a 1.8 with a mean rank 3.85.Conclusion : The optimal use value Sensitivity Encoding (SENSE) on T2-weighted sequences for optimal BTFE MRCP is a 1.8.